2020
DOI: 10.1101/2020.05.05.079467
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Resolving spatial complexities of hybridization in the context of the gray zone of speciation in North American ratsnakes (Pantherophis obsoletuscomplex)

Abstract: 29Estimating species divergence with gene flow has been crucial for characterizing the gray 30 zone of speciation, which is the period of time where lineages have diverged but have not yet 31 achieved strict reproductive isolation. However, estimates of divergence times and gene flow 32 often ignores spatial information, for example the formation and shape of hybrid zones. Using 33 population genomic data from the eastern ratsnake complex (Pantherophis obsoletus), we infer 34 phylogeographic groups, gene flow,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 144 publications
0
8
0
Order By: Relevance
“…Species delimitation is a challenge that cannot be easily settled by computational algorithms alone (Carstens et al, 2013; Padial et al, 2010; Sukumaran & Knowles, 2017). The interplay of stochastic coalescent variation (Knowles & Carstens, 2007), introgression (Martin et al, 2013), and spatial and ecological barriers to gene flow (Burbrink et al, 2021) can yield strikingly complex scenarios in the “gray zone” of speciation (Matute & Cooper, 2021; de Queiroz, 2007). Accordingly, a range of these scenarios is observed here in Desmognathus .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Species delimitation is a challenge that cannot be easily settled by computational algorithms alone (Carstens et al, 2013; Padial et al, 2010; Sukumaran & Knowles, 2017). The interplay of stochastic coalescent variation (Knowles & Carstens, 2007), introgression (Martin et al, 2013), and spatial and ecological barriers to gene flow (Burbrink et al, 2021) can yield strikingly complex scenarios in the “gray zone” of speciation (Matute & Cooper, 2021; de Queiroz, 2007). Accordingly, a range of these scenarios is observed here in Desmognathus .…”
Section: Discussionmentioning
confidence: 99%
“…Second, which of these candidate species or phylogeographic lineages show evidence of hybridization across the nuclear and mitochondrial genomes, and what is the spatial extent of present‐day hybrid zones (Burbrink et al, 2021; Szymura & Barton, 1986)? The existence, location, and width of these geographic admixture zones may vary significantly among species pairs and loci (Barton, 1983; Dufresnes et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Changes in hybrid zone shapes and locations over time might be common (Buggs, 2007; Ryan et al, 2018; Wielstra, 2019), as revealed by evidence from the fossil and pollen records, niche modeling through time, displacement of extant populations of one species from the expanding range of another, or genome‐wide evidence from displaced lineages. There is ample evidence that hybrid zones of various shapes and sizes have existed from the present through to the late Miocene between extant species (Barth et al, 2020; Burbrink et al, 2021; Hewitt, 2011). In birds, fertile hybrids can be produced well past speciation, even among taxa sharing a common ancestor more than 17 million years ago (Prager & Wilson, 1975; Price & Bouvier, 2002).…”
Section: Brief History Of Subspecies and Reproductive Isolationmentioning
confidence: 99%
“…In some groups, degree of reproductive isolation scales with time of divergence (Bolnick & Near, 2005; Singhal & Moritz, 2013), but not in others (Burbrink et al, 2021). Pre‐ and postzygotic isolation may also accumulate at different rates (Stelkens et al, 2010; Uy et al, 2018).…”
Section: Introduction: Gene Flow and The Species Problemmentioning
confidence: 99%
“…Here we show that computer vision algorithms have low power to distinguish at least some putative species that have been delineated primarily using molecular methods and where training data were identified exclusively from photos, presumably primarily based on geographic location (Table 2). Although Burbrink (2001) provided multivariate analyses of 67 mensural and meristic characters (mostly related to scalation) that corresponded to mitochondrial lineages, the most obvious color and pattern variants intergrade with one another over large areas and correspond to former subspecies designations rather than Burbrink's species concepts (recently refined to better match phenotypic variation; Burbrink et al, 2020;Hillis and Wüster, 2021), and numerous color patterns can be found within each putative species, especially P. alleghaniensis (not to mention the marked ontogenetic change characteristic of all three, wherein juveniles are most similar to adult P. spiloides from the southern portion of their range). This, combined with the widely overlapping distribution between P. alleghaniensis and P. spiloides, makes the three putative species nearly impossible for both humans and AI to differentiate in the absence of information about geographic location.…”
Section: Patterns Across Test Datasetsmentioning
confidence: 99%